Implementation of Information Technology-Based Learning Media in Islamic Religious Education Subjects at Masyithoh Kroya SMP, Cilacap Regency - Ngadiman, Ngadiman; Fauzi, Fauzi (Budapest International Research and Critics University, 2021)
This study aims to determine the implementation of IT-based learning media in PAI subjects at Masyithoh Kroya Middle School, Cilacap Regency. The research method used is using a qualitative-descriptive approach, namely the implementation of IT-based learning media on PAI subjects. The research was conducted from October 1 to October 15, 2021. The data collection techniques used were interviews and documentation. In-depth interviews aim to dig up the necessary data. Researchers prepared a number of questions to respondents regarding the implementation of IT-based media in PAI learning. Based on the results and discussion of the research, it can be concluded that the media in learning Islam at Masyithoh Kroya Middle School in intensive class requires learning media, namely PowerPoint, GOM Player, KM Player, Media Player and Youtube.